Design of the Paper Flowerpot Automatic Eyeletter Mechanism - Li Ruifeng; Yao Ligang; He Jiaying; Ji Wentao (Jixie chuandong)
Aiming at the problem of the high labor intensity,low eyeleting precision and low work efficiency of conventional paper flowerpot eyeletter with manual operation,an automatic eyeletter is proposed. And then,through building the mathematic model,the analysis and optimization of this mechanical structure is carried out by using mathematic analytic software. At last,two cam contour curves meeting the requirement of cam mechanism motion law well is designed. As a result,a strong theoretical basis for further study and object production in the future is provided.